OPTIMALISASI SENTRA HAK KEKAYAAN INTELEKTUAL DALAM MENINGKATKAN POTENSI EKONOMI PERGURUAN TINGGI: FADLAN KALMA, S.Th.I, MH - fadlan kalma fadlan (LPPM STIA Nusantara Sakti, 2020)
With various aspects related to intellectual property owned, universities have great potential to produce high quality intellectual property by implementing Universities Tridharma, namely teaching, research and community devotion loaded with intellectual property, both from input, in process and output. To manage, protect and utilize the Intellectual Property, each university should strive to establish an Intellectual Property Center in its environment in accordance with its capacity. In optimizing IPR centers in increasing the economic potential of tertiary institutions, it can be done by commercializing research results and Intellectual property licenses